PWE-017 A multi-disciplinary approach to percutaneous endoscopic gastrostomy insertion in motor neurone disease. (June 2019) - Reddy, A; Anderson, S; Arrandale, L; Dunn, J; Marino, P; Murphy, PB; Steier, J; Suh, ES; Thomas, H; Yin, L; Ramsay, M; Hart, N; et al.
Abstract : Weight loss and bulbar dysfunction is common in motor neurone disease (MND). Gastrostomy placement is complex in this cohort. Percutaneous endoscopic gastrostomy (PEG) is reported as the favoured approach in patients without chronic respiratory failure with radiologically inserted gastrostomy insertion reserved for patients with severe respiratory compromise. The aim of this study was to evaluate the outcome for patients with MND receiving PEG insertion as part of a multidisciplinary team approach in a respiratory intensive care unit setting. A retrospective observational study was conducted on MND patients on non-invasive ventilation (NIV) who were admitted for PEG insertion between September 2014 and April 2018. PEG were inserted with intravenous anaesthesia and analgesia (propofol infusion and fentanyl blouses) plus local anaesthesia to skin (lidocaine 1%) using non-invasive mechanical ventilation on pressure-control mode. Fifty-nine PEG insertions were performed successfully in MND patients requiring NIV and all patients discharged from hospital. Subjects (37 males) had age 65±11 years. Six (10%) were quaternary referrals following failed PEG insertion. Length of stay was 5±5 days. Body mass index (BMI) at diagnosis was 27±5 kg/m2 with BMI at PEG insertion 22±4 kg/m2. Mean weight change from diagnosis to insertion was -16±10%. Ventilator compliance time was 3±6 hours. Eighteen patients were compliant to NIV (NIV usage>4 h daily). Thirty-day mortality was 10% and 90-day mortality was 15%. Survival time since MND diagnosis for non-complaint to NIV patients (859±123 days) trended to be less than those compliant to NIV (1165±203) (p=0.058) (Figure 1). PEG insertion in MND patients requiring NIV is safe and effective. NIV compliance in this cohort of patients who have bulbar dysfunction might affect survival.